2000
DOI: 10.1161/01.str.31.4.946
|View full text |Cite
|
Sign up to set email alerts
|

Transient and Permanent Resolution of Ischemic Lesions on Diffusion-Weighted Imaging After Brief Periods of Focal Ischemia in Rats

Abstract: Background and Purpose-The early ischemic lesions demonstrated by diffusion-weighted imaging (DWI) are potentially reversible. The purposes of this study were to determine whether resolution of initial DWI lesions is transient or permanent after different brief periods of focal brain ischemia and to evaluate histological outcomes. Methods-Sixteen rats were subjected to 10 minutes (nϭ7) or 30 minutes (nϭ7) of temporary middle cerebral artery occlusion or sham operation (nϭ2). DWI, perfusion-weighted imaging (PW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
171
1
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 216 publications
(187 citation statements)
references
References 62 publications
14
171
1
1
Order By: Relevance
“…Experimentally, areas that develop histopathological SNL X48 hours after tMCAo regularly display apparent diffusion coefficient/diffusion-weighted imaging (DWI) lesions acutely, indicating severe ischemia. 37,40,42 Diffusionweighted imaging lesions affected by SNL completely vanish after reperfusion 37,42 and do not reappear secondarily 42 (Figure 4). Conversely, DWI lesions that reappear secondarily are generally T2-hyperintense and exhibit pannecrosis histopathologically, 40,41 although very severe SNL in the caudoputamen has been reported in some rats with this imaging pattern 40 (Figure 4).…”
Section: Animal Modelsmentioning
confidence: 96%
See 1 more Smart Citation
“…Experimentally, areas that develop histopathological SNL X48 hours after tMCAo regularly display apparent diffusion coefficient/diffusion-weighted imaging (DWI) lesions acutely, indicating severe ischemia. 37,40,42 Diffusionweighted imaging lesions affected by SNL completely vanish after reperfusion 37,42 and do not reappear secondarily 42 (Figure 4). Conversely, DWI lesions that reappear secondarily are generally T2-hyperintense and exhibit pannecrosis histopathologically, 40,41 although very severe SNL in the caudoputamen has been reported in some rats with this imaging pattern 40 (Figure 4).…”
Section: Animal Modelsmentioning
confidence: 96%
“…Histopathology showed moderate selective neuronal death (4% to 28% necrotic neurons) in the caudoputamen with no instance of infarction in the 10-minute group, and massive neuronal death or pannecrosis in all 30-minute group subjects (88% to 100% necrotic neurons). From Li et al, 40 with permission. eventual outcome in man.…”
Section: Animal Modelsmentioning
confidence: 99%
“…Lastly, since the ISEL procedure stains predominantly apoptotic (and to a lesser degree necrotic) cells (Wijsman et al, 1993), H&E staining was used to exemplarily confirm cell death. Briefly, neurons were classified as necrotic when they exhibited pyknosis, karyorrhexis, karyolysis, cytoplasmic eosinophilia ('red neuron'), or loss of affinity for hematoxylin ('ghost neuron') (Li et al, 2000). Apoptotic neurons were identified by the criteria of Li et al (1998b), that is, via the presence of membrane-bound apoptotic bodies of roughly round or ovoid shape.…”
Section: Histologymentioning
confidence: 99%
“…Additionally, depending on the duration of the occlusion, secondary abnormalities may develop on diffusion-weighted imaging (DWI) and T 2 -weighted imaging (T2WI) (Li et al, 2000;Neumann-Haefelin et al, 2000). These findings are intriguing as both transient and permanent resolution of such abnormalities was observed in SSD patients (Baird et al, 1995;Fujioka et al, 1999a;Kraemer et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…As it has been shown that severe dysfunctions in cerebral activity and neurobehavior can persist despite normal appearing brain on DWI, perfusion-weighted imaging (PWI), and T2WI , further research is warranted to understand the mechanisms underlying SSD. However, most experimental data regarding transient MCAO were derived with suture MCAO models (Li et al, 2000;Neumann-Haefelin et al, 2000;Sicard et al, 2006), which do not reliably reproduce the inhomogeneous vascular findings in patients suffering from acute territorial stroke (Adams et al, 2005).…”
Section: Introductionmentioning
confidence: 99%